Immunogenicity of the 9-valent human papillomavirus vaccine: Post hoc analysis from five phase 3 studies - Anna R. Giuliano; Joel M. Palefsky; Stephen E. Goldstone; Jacob Bornstein; Ilse De Coster; Ana María Guevara; Ole Mogensen; Andrea Schilling; Pierre Van Damme; Corinne Vandermeulen; Misoo C. Ellison; Susan Kaplan; et al. (Human Vaccines & Immunotherapeutics)
Post hoc analyses of 9-valent human papillomavirus (9vHPV) vaccine immunogenicity were conducted in five Phase 3 studies that enrolled males. Month 7 antibody geometric mean titers (GMTs) after three 9vHPV vaccine doses were analyzed in 10,024 males/females aged 16–26 years from studies 001 (NCT00543543), 002 (NCT00943722), 003 (NCT01651949), and 020 (NCT02114385). Covariates considered were age, gender, sexual orientation, region of residence, and race. GMTs among 2599 males/females aged 9–15 years (studies 002 and 010 [NCT01984697]) were assessed 6 months after one, two, and three 9vHPV vaccine doses. 9vHPV vaccine immunogenicity was robust across populations. Month 7 GMTs were generally higher in participants aged 16–21 versus 22–26 years. Region and race minimally impacted immunogenicity. Adjusted integrated analysis showed lower immunogenicity in men who have sex with men (MSM) versus heterosexual men (HM) for nine HPV types, and higher immunogenicity in HM versus females for seven HPV types. Among 9–15-year-olds, trends toward higher GMTs in males versus females post-Dose 3, similar GMTs post-Dose 2, and lower post-Dose 1 were observed. In conclusion, 9vHPV vaccine immunogenicity was robust in males aged 16–26 years across a range of baseline characteristics. GMT ratios for males versus females aged 9–15 years tended to increase with more doses.